Pendayagunaan Infaq Masjid Besar Al-Muamalah Untuk Memaksimalkan Peran Masjid Terhadap Masyarakat - Muhammad Hasibuddin; Jamiah Tompo (Universitas Muslim Indonesia, 2022)
Indonesia as a country with the largest Muslim majority in the world, certainly has a large number of mosques. Unfortunately, the number of mosques is not accompanied by an increase in the quality of the mosque itself. Although physically, the mosque has undergone a significant evolution in various aspects, such as the quality of the building, the facilities are magnificent and luxurious. However, the quality of the congregation tends to stagnate and even decline. This research approach is field research (Field Research) where the compiler will collect data by going directly to the field, community, group or institution that is the object of research to study intensively the various problems being studied. The results of the study found two principles of mosque management that the researchers wanted to highlight and underline as something that should be appreciated and even imitated by the administrators of the Muamalah Mosque. First, do not deposit congregational funds but distribute them as quickly as possible. And second, the principle is to make the congregation comfortable and always want to come back to the mosque.